Ceratricula and Flandria—two new genera of Afrotropical Hesperiidae (Hesperiinae (incertae sedis)) for species currently placed in the genus Ceratrichia Butler - Larsen, Torben B. (Zootaxa, 2013)
Two genera of Afrotropical Hesperiidae are described to receive species currently placed in Ceratrichia Butler, where they do not belong. Ceratricula gen. nov. comprises a single species spanning most of the main rainforest zone from Sierra Leone to Uganda and south to Zambia in three subspecies, ssp. congdoni ssp. nov. being new and ssp. indeterminabilis Strand raised from synonymy. Flandria gen. nov. consists of three rare or very rare species that are limited to eastern Cam-eroun and the western Democratic Republic of Congo, which gives this genus a more restricted range than any other among the African forest skippers; the three Flandria had previously been placed in Ceratrichia, Pardaleodes, or Andro-nymus.